Ondel-Ondel Local Content Curriculum as A Vocational School of Betawi Cultural Preservation - Aji Cahya Gumelar; Fatihah Ekawati; Fitriani Intan Purnamasari; Zharra Cynthia Dewi (research, training and philanthropy institution Natural Aceh, 2021)
The research objective was to implement the learning process ondel-ondel arts in local content in the form of music, dance, and fine art compositions at the Vocational High School level as an effort to preserve Betawi culture. This research was conducted using a qualitative approach with interview techniques, observation, literature study, and triangulation techniques. Music composition for ondel-ondel art only relies on the trumpet as an instrument that plays a melody or song. The song that was played was limited to only 2 songs, namely Leles and Mangle. Ondel-ondel art in terms of visual art, students are able to make ondel-ondel masks using recycled materials, besides that in terms of the ondel-ondel art dance uses free movements that can be pulled by students at a show using several musical instruments that are still maintained until now. The implementation of local content in schools provides provisions for knowledge, skills, behavioral orders and student behavior, in the form of insight into environmental conditions and local wisdom